Nepali Students’ Anxiety in the EFL Classroom: Recognizing its Reasons, Reactions, and Coping Strategies - Dewan, Shankar (English Language Teaching Perspectives, 2025)
English as foreign language (EFL) classrooms are generally prone to anxiety-arousal, making foreign language learning a challenging experience for many students. Most learners often encounter anxiety in the EFL settings. This quantitative survey study aimed to identify the causes of anxiety experienced by Nepali students in the EFL classroom, their reactions during anxious situations, and the strategies they adopted to cope. Using three different sets of questionnaires, data were collected from ninety randomly selected B.Ed. and BBS students from two community campuses in the Morang district. The findings revealed that the key common anxiety-causing factors included fear of failing the class, incomprehensible input or difficulty in understanding the teacher’s language/instruction, and lack of preparation; students’ reactions to anxiety incorporated faster heart beating, changes in facial expression, mind going blank, difficulties in concentration, and changes in breathing; and students mainly relied on preparation and relaxation strategies to cope with their anxiety. This study provides valuable insights for policymakers, curriculum designers, teachers, and students on the causes of foreign language anxiety, students’ reactions to it, and its coping strategies.